Method for preparing carbon dioxide-based building material by mineralizing carbon dioxide trapping liquid

By conducting solid-liquid homogeneous mineralization reaction between CO2 trap liquid and calcium-containing minerals, and forming carbon dioxide-based building materials through hydrothermal reaction, the problems of high energy consumption of CO2 trapping and purification and the risk of storage CO2 leakage in the prior art are solved, and efficient and large-scale CO2 fixation and resource utilization are achieved.

CN119874326APending Publication Date: 2025-04-25TONGJI UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311383070.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-24
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

In the existing carbon dioxide capture, utilization and storage technologies, the CO2 capture and purification process consumes high energy, and there is a risk of leakage in the storage of CO2, so resource reuse cannot be achieved.

Method used

Directly conducting solid-liquid homogeneous mineralization reaction between CO2 trap liquid and calcium-containing minerals to prepare calcium carbonate mineralization products, and form carbon dioxide-based building materials through hydrothermal reactions to achieve efficient, large-scale fixation and resource reuse of CO2.

Benefits of technology

This method does not require gaseous purification of CO2, shortens the process carbon chain, reduces energy consumption, achieves a high fixed rate (>25%) and stable storage of CO2, and then uses CO2 as a building material, which has industrial value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119874326A_ABST
    Figure CN119874326A_ABST
Patent Text Reader

Abstract

The invention relates to a method for preparing a carbon dioxide-based building material by mineralizing a carbon dioxide trapping liquid. The method for preparing the carbon dioxide-based building material from the mineralized carbon dioxide capture liquid comprises the following steps: carrying out solid-liquid homogeneous mineralization reaction on the carbon dioxide capture liquid and a calcium-containing raw material to obtain a calcium carbonate mineralized product; and mixing the calcium carbonate mineralization product, a silicon-containing raw material and a solvent to form slurry, carrying out molding and demolding to obtain a demolding block body, and then carrying out a hydrothermal reaction on the demolding block body to obtain the carbon dioxide-based building material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of carbon dioxide fixation and utilization, and specifically relates to a method for preparing carbon dioxide-based building materials from mineralized carbon dioxide capture liquid. Background Art

[0002] Carbon dioxide capture, utilization and storage (CCUS) is a technology that can reduce carbon emissions on a large scale. Carbon dioxide capture and storage (CCS) is a technology that captures CO2 from flue gas, tail gas or air, purifies it, compresses it into liquid CO2 and injects it into the ground or the seabed for storage. Among them, carbon dioxide capture mainly adopts chemical absorption method, and the absorbent is mainly alkaline solvents such as pure amines, carbonate solution, NaOH solution, and ammonia water. Since CCS technology requires the CO2 capture liquid to be analyzed and purified into CO2, the operating cost and energy consumption of this technology remain high. In addition, there is a huge risk of leakage and environmental and ecological impact when storing CO2 underground and on the seabed, and the storage of CO2 does not achieve the effect of resource reuse. Therefore, it is necessary to improve and expand the above-mentioned technologies to cope with the increasingly severe problem of carbon emission reduction.

[0003] Carbon dioxide mineralization is a method of using divalent metal elements such as calcium and magnesium in active minerals or solid waste to react with CO2 gas or solution to obtain stable carbonate minerals, thereby realizing the storage, fixation and reuse of CO2. Chinese patent (CN109399675A) discloses a method for mineralizing and storing CO2 using serpentine. The patent extracts magnesium ions from serpentine by acid leaching and blows high-purity CO2 gas into a magnesium ion solution to prepare nano-magnesium carbonate crystals by crystallization. Although this method can effectively utilize mineral resources such as serpentine and produce high-value nanocrystals, its CO2 source is mainly high-purity gas. The capture, purification and analysis of carbon dioxide leads to high energy consumption of the technology. Moreover, the use of only serpentine and other minerals to prepare the obtained nanocrystals also limits the scope of application of the technology, and it is impossible to absorb the annual CO2 emissions of tens of billions of tons. Chinese patent (CN108340480B) discloses a method for curing concrete blocks with carbon dioxide cascade mineralization, which utilizes free calcium (Ca) in concrete to produce high-value nanocrystals. 2+ ) mineralizes CO2 and achieves a mineralization and fixation effect. This technology blows purified CO2 gas onto the surface of the concrete embryo, causing it to react with the surface calcium to form calcium carbonate, which has the effect of enhancing strength and fixing CO2. Since building materials are usually dense, it is difficult for CO2 gas to diffuse into the inner layer of the embryo, resulting in CO2 mineralization occurring only on the surface, greatly limiting its CO2 fixation amount.

[0004] In general, the existing carbon dioxide capture, utilization and storage technologies mostly use the captured and desorbed CO2 gas as the carbon source, which leads to the excessively long carbon chain of CCUS technology (CO2-CO3 2-—CO2—CO3 2- —CaCO3), with low fixation efficiency and high energy consumption. CaCO3 building materials are used as the terminal product of carbon dioxide mineralization. They can absorb tens of billions of tons of CO2 and realize resource utilization by relying on hundreds of billions of tons of building materials each year. Therefore, it is necessary to develop a new technology that is more efficient in mineralization and fixation of large amounts of CO2 as building materials. Summary of the invention

[0005] In view of the above technical problems, the purpose of the present invention is to provide a method for mineralizing carbon dioxide with simple process and low cost. The method directly uses CO2 capture liquid as the source of CO2, and cooperates with calcium-containing minerals to mineralize CO2 as building materials, realizes resource storage and reuse, and achieves the effect of efficient and large-scale fixation of CO2.

[0006] In a first aspect, the present invention provides a method for preparing a carbon dioxide-based building material by mineralizing carbon dioxide capture liquid, the method comprising the following steps: The carbon dioxide capture liquid and the calcium-containing raw material are subjected to a solid-liquid homogeneous mineralization reaction to obtain a calcium carbonate mineralization product; The calcium carbonate mineralization product, silicon-containing raw materials and solvent are mixed to form a slurry, which is then formed and demolded to obtain a demolding body, and then the demolding body is subjected to a hydrothermal reaction to obtain the carbon dioxide-based building material.

[0007] Preferably, the carbon dioxide capture liquid is an ammonium carbonate solution, and the mass fraction of the ammonium carbonate solution is 10-40wt%, preferably 33wt%.

[0008] Preferably, the calcium content of the calcium-containing raw material is 10-54wt%; preferably, the calcium-containing raw material is solid waste carbide slag, fly ash, steel slag; more preferably, the particle size of the calcium-containing raw material is 3-100μm, and the average particle size d 50 It is 17.57μm.

[0009] Preferably, the ratio of the carbon dioxide capture liquid to the calcium-containing raw material is 1-10 mL / g, preferably 4 mL / g.

[0010] Preferably, the temperature of the solid-liquid homogeneous mineralization reaction is 25-80°C, and the time is 1-16 hours, preferably 1-12 hours, and more preferably 1 hour.

[0011] Preferably, the silicon content in the silicon-containing raw material is 10-46.7wt%; preferably, the silicon-containing raw material is waste glass powder obtained by crushing and grinding daily glass slag, and the chemical composition of the waste glass powder preferably includes: SiO268.09%, Na2O 17.37%, by mass percentage; the particle size of the silicon-containing raw material is distributed in the range of 60-120μm, and the preferred average particle size is 88.9μm.

[0012] Preferably, based on the total mass of the mineralized product and the silicon-containing raw material as 100%, the mass of the mineralized product accounts for 30-70%, preferably 60%, and the mass of the silicon-containing raw material accounts for 70-30%, preferably 40%; the solvent accounts for 5-15% of the total mass of the mineralized product and the silicon-containing raw material.

[0013] Preferably, the temperature of the hydrothermal reaction is 100 to 220° C., preferably 120 to 220° C.; the time of the hydrothermal reaction is 3 to 12 h, preferably 6 to 12 h, more preferably 9 h.

[0014] In a second aspect, the present invention provides a carbon dioxide-based building material obtained according to the above preparation method.

[0015] Beneficial Effects 1) The present invention directly utilizes the captured CO2 solution without the need for a complicated process of purifying it into a gaseous state; 2) The present invention can mineralize CO2 in the material (not on the surface of the material) to the maximum extent possible and avoid the high energy consumption caused by the lengthy carbon chain structure; 3) The present invention simulates the principle of underground sedimentary rocks, and uses low-temperature hydrothermal technology to synthesize CO2-fixed materials into CO2-based building materials. Since CO2 can be evenly and stably distributed in its solidified materials in the form of calcium carbonate, CO2-based building materials with a high fixation rate (>25%) can be achieved, and CO2 fixation, storage and reuse can be achieved at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 Schematic diagram of carbon content of homogeneous mineralization products under different liquid-to-solid ratios in Examples 1 and 2; Figure 2 Schematic diagram of carbon content of homogeneous mineralization products at different mineralization times in Examples 1 and 3; Figure 3 This is a SEM image of the homogeneous mineralized product sample prepared in Example 1; Figure 4 Schematic diagram of the change in flexural strength of carbon dioxide-based building materials under different waste glass powder dosages in Examples 1 and 4; Figure 5 Schematic diagram of the change in flexural strength of carbon dioxide-based building materials at different hydrothermal temperatures in Examples 1 and 5; Figure 6 Schematic diagram of the change in flexural strength of carbon dioxide-based building materials (solidified blocks) at different hydrothermal reaction times in Examples 1 and 6; Figure 7 XRD patterns of solidified block samples obtained under different hydrothermal solidification time conditions in Examples 1 and 6; Figure 8This is the thermogravimetric analysis diagram of the solidified block sample prepared under the condition of hydrothermal solidification time of 9 hours in Example 1. DETAILED DESCRIPTION

[0017] The present invention is further described below by way of embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, but not to limit the present invention.

[0018] The following is an exemplary description of the method for preparing carbon dioxide-based building materials using the mineralized carbon dioxide capture liquid provided by the present invention. The preparation method may include the following steps.

[0019] (1) Mineralization reaction. Add the carbon dioxide capture liquid and the calcium-containing raw material into the solid-liquid homogeneous reactor to carry out a solid-liquid homogeneous mineralization reaction. After the reaction is completed, filter and dry to obtain a calcium carbonate mineralization product (also called "CO2 fixed material").

[0020] The carbon dioxide capture liquid refers to a solution containing carbon components obtained after the alkaline absorbent in the carbon dioxide capture system absorbs gaseous carbon dioxide. In some embodiments, the CO2 capture liquid can be an ammonium carbonate solution; wherein the mass fraction of the ammonium carbonate solution can be 10 to 40wt%, preferably 33wt%.

[0021] In some embodiments, the calcium content of the calcium-containing raw material can be 10-54wt%; preferably, the calcium-containing raw material can be solid waste such as carbide slag, fly ash, steel slag and other solid wastes containing more calcium; more preferably, the particle size of the calcium-containing raw material can be 3-100μm (140-500 mesh, such as 200 mesh), and the average particle size d 50 It can be 17.57μm.

[0022] The carbide slag is obtained by dehydrating, drying and screening the carbide slag slurry produced in the process of producing polyvinyl chloride by the carbide method, and its main component is hydroxyl calcium hydroxide crystal type calcium hydroxide; wherein the chemical composition of the carbide slag may include: by mass percentage, CaO 80-100%, SiO2 0-15%, Al2O3 0-5%, preferably CaO 93.92-98.52%, SiO2 0.58%, Al2O3 0.33%. The fly ash is the fine solid particle ash collected and captured in the flue gas after coal combustion, and is the main solid waste discharged by coal-fired power plants; wherein the chemical composition of the fly ash may include: by mass percentage, CaO 5-10%, SiO2 40-60%, Al2O3 35-50%, preferably CaO 6%, SiO2 55%, Al2O3 39%. The steel slag is an alkaline industrial solid waste associated with the steelmaking process; wherein the chemical composition of the steel slag may include: in mass percentage, CaO 5-35%, SiO2 5-30%, Al2O3 10-20%, Fe2O3 25-50%, preferably CaO 35%, SiO2 25%, Al2O3 15%, Fe2O3 25%.

[0023] In some embodiments, the dosage ratio (liquid-to-solid ratio) of the carbon dioxide capture liquid to the calcium-containing raw material can be 1 to 10 mL / g, preferably 4 mL / g. Among them, if the liquid-to-solid ratio is too low, the calcium carbonate content in the mineralized product will be low; if the liquid-to-solid ratio is too high, it will lead to waste of carbon dioxide capture liquid, and the high dosage ratio will not significantly increase the calcium carbonate content in the mineralized product. The homogeneous mineralization reaction carried out in the preparation method step (1) provided in the present invention is essentially a solid-liquid reaction, and the progress of the reaction mainly depends on two factors: 1) solid-liquid contact area: the larger the solid-liquid contact area, the more liquid molecules are exposed to the surface of the solid particles, the higher the degree of reaction, and the faster the speed; 2) solid particle activity: the size of the particles determines the activity of the molecules on the surface of the particles and the strength of their material exchange. The liquid molecules in the mineralization reaction of the present invention are extremely active, so the main factor limiting the progress of the solid-liquid reaction is the size of the solid particles.

[0024] In some embodiments, the temperature of the solid-liquid homogeneous mineralization reaction may be 25 to 80° C., and the time may be 1 to 16 hours, preferably 1 to 12 hours, and more preferably 1 hour.

[0025] The drying temperature may be 40-105°C, preferably 80°C.

[0026] In some embodiments, the mass fraction of calcium carbonate in the chemical composition of the calcium carbonate mineralization product is 22 to 100%, preferably 62 to 90.7%. Controlling the higher content of calcium carbonate in the mineralization product can promote more calcium dissolution during the hydrothermal solidification process described later, and can also ensure that more carbon dioxide is fixed in the final product.

[0027] In some embodiments, the calcium carbonate mineralization product is mainly a calcite structure, a small part of which is an aragonite structure, and has a complete crystal structure; the grain size range is 5-200 μm, and the average grain size is 12.5 μm.

[0028] Among them, in the mineralization reaction carried out in the step (1), the mechanism of the homogeneous mineralization reaction of the CO2 capture liquid (ammonium carbonate solution, etc.) and calcium-containing raw materials such as carbide slag is embodied in the following: kinetic studies have shown that the homogeneous mineralization reaction process is controlled by three control mechanisms: mass transfer diffusion, product layer diffusion and chemical reaction. Among them, since the calcium-containing raw material particles are fine, the calcium ions inside the particles are easier to diffuse to the particle surface, and the CO3 in the CO2 capture liquid 2- Diffusion to the surface of calcium-containing raw material particles is also easy to occur, and the diffusion speed of both is fast, so it is different from the surface mineralization of the mineralization curing in the prior art; the mineralization degree in the solid-liquid homogeneous reaction adopted in the present invention is deeper, so more CO3 in the capture liquid can be captured. 2- Converted into carbonate to achieve maximum mineralization effect. At the same time, homogeneous mineralization reaction can provide a higher solid-liquid contact area, and CO3 2- It can quickly combine with calcium ions to form a stable calcium carbonate product, so that the reaction can obtain a large amount of calcium carbonate products in a short time, so the constant of chemical reaction control in the kinetic fitting result is significantly higher than the other two control mechanism constants by one order of magnitude. Therefore, the excellent mineralization effect in step (1) is due to the highly active solid waste calcium carbide slag and other calcium-containing raw materials and solid-liquid homogeneous mineralization conditions. The calcium-containing raw materials can provide sufficient calcium, and the homogeneous reaction ensures that the carbonate ions in the capture solution can quickly and massively combine with calcium ions to generate calcium carbonate products.

[0029] (2) Hydrothermal reinforcement: The calcium carbonate mineralization product, silicon-containing raw materials and solvent are mixed to form a slurry, which is then molded and demolded to obtain a demoldable body, and then the demoldable body is subjected to a hydrothermal reaction to obtain the carbon dioxide-based building material.

[0030] In some embodiments, the silicon content in the silicon-containing raw material may be 10-46.7 wt%; preferably, the silicon-containing raw material may be waste glass powder obtained by crushing and grinding glass slag in daily life. Preferably, the chemical composition of the waste glass powder may include: SiO2 68.09%, Na2O 17.37% by mass percentage. The particle size distribution of the silicon-containing raw material may be 60-120 μm; preferably, the average particle size may be 88.9 μm.

[0031] The solvent may be water. In some embodiments, based on the total mass of the mineralized product and the silicon-containing raw material as 100%, the mass proportion of the mineralized product may be 30-70%, preferably 60%, and the mass proportion of the silicon-containing raw material may be 70-30%, preferably 40%; the solvent may be 5-15% of the total mass of the mineralized product and the silicon-containing raw material.

[0032] It should be noted that in the hydrothermal curing process of step (2) of the preparation method provided by the present invention, the strength is provided by the CSH (calcium silicate hydrate) product in the early stage, and then the CSH develops into a complete crystal such as tobermorite and other calcium silicate products to further enhance the strength. Generally speaking, the calcium silicate hydrate product is most easily generated when the raw material calcium-silicon ratio (molar ratio) is close to 0.87, and its contribution to strength is also the greatest.

[0033] In some embodiments, the molding pressure may be 10 to 30 MPa.

[0034] In some embodiments, the temperature of the hydrothermal reaction can be 100-220°C, preferably 120-220°C; the time of the hydrothermal reaction can be 3-12h, preferably 6-12h, and more preferably 9h. Among them, if the hydrothermal reaction temperature is too high, a large amount of siliceous dissolution will occur, the crystals will grow excessively, and the pores of the mineralized product will be squeezed, resulting in internal stress, easy cracking of the sample, and reduced strength; if the reaction temperature is too low, it will not be enough to stimulate the gradual dissolution of the siliceous particles or only a very small number of particles have a high surface activation energy and partially dissolve, and the amount of siliceous dissolution is too small, resulting in the inability to generate hydration reinforcement products. The mineralized product particles still show a simple stacking state without cross-linking, which is very easy to crack. If the reaction time is too long, the hydration reinforcement product will continue to grow, the grains will be too large, and the mineralized product will produce expansion internal stress inside, and the strength will be reduced; if the reaction time is too short, the hydration reinforcement product will not be effectively generated in a short time and the cross-linked particles will not promote the improvement of the strength of the mineralized product.

[0035] In the hydrothermal strengthening reaction carried out in step (2), the curing mechanism of the mineralized product and the silicon-containing raw material is embodied in the following aspects: the hydrothermal curing adopted by the present invention simulates the diagenetic mechanism of sedimentary rocks, the minerals dissolve / precipitate under the hydrothermal environment, and directional generation of substances such as calcium silicate hydrates enhances the strength of the matrix; the degree of hydrothermal curing in the present invention depends on the dissolution progress of the siliceous raw material, and the fast dissolution rate and high degree of the hydrothermal curing can form calcium silicate hydrate products such as CSH and tobermorite in a very short time, thereby enhancing the strength of the cured body; and the hydrothermal dissolution process in the present invention mainly occurs in the calcium carbonate particles. The surface layer and the gaps can retain the original composition and structure of most of the particles; in contrast, the mineralized product in the present invention is mainly calcium carbonate, wherein the mineralized product provides a small amount of calcium to participate in the hydrothermal process, and reacts with the liquid phase silicon dissolved in the gaps between the particles by silicon-containing raw materials such as waste glass powder to form calcium silicate hydrate, which then fills the pores of the calcium carbonate particles, so that the large gaps between the calcium carbonate particles become small gaps, and the matrix pore structure is optimized; and, due to the gel cross-linking effect of the calcium silicate hydrate and the interlacing effect of the crystal particles, the calcium carbonate particles are tightly fixed together, thereby achieving the overall strength enhancement of the de-module body. At the same time, due to the low-temperature hydrothermal conditions, most of the calcium carbonate in the mineralized product will not decompose, thus achieving the stable homogeneous storage and reuse of CO2.

[0036] Based on the two steps in the preparation method provided by the present invention, the determining factors of the reinforcement process in step (2) are the amount of silicon and calcium dissolved and precipitated under the hydrothermal environment and the amount of calcium silicate hydrate product formed by the combination of the two, and the dissolution of calcium and silicon is related to their own physicochemical properties (particle size, mineral composition, crystal integrity), hydrothermal environment, and hydrothermal time. Among them, on the one hand, the particle size will affect the difficulty and speed of dissolution of silicon and calcium on the surface of the particles; on the other hand, large particles will make cross-linking between particles more difficult, and small particles can form a hard material under the cross-linking effect of a small amount of calcium silicate hydrate product. Therefore, if the physicochemical properties of the mineralized product obtained by mineralization in step (1) are not good (such as the particles are too large, the mineral crystal form is not good, and it is easy to be destroyed under pressure), it will affect the hydration process of step (2), resulting in a decrease in the strength of the final material. For example, if the calcium carbonate in the mineralized product obtained in step (1) is amorphous calcium carbonate, that is, the mineral crystal form is poor, the overall strength of the matrix will be weak. Although it can be cross-linked by the hydrated calcium silicate product, when it is compressed, cracks will preferentially occur and continue to expand at the amorphous calcium carbonate, rather than at the intergranular gaps. The sample strength will not be rapidly improved due to the generation of hydration products. Similarly, if the mineralized product particles obtained in step (1) are coarse, on the one hand, the surface excitation energy of large-particle calcium carbonate is high, and its surface calcium is difficult to precipitate into the interstitial liquid phase, resulting in a small amount of hydration products; on the other hand, more large particles will cause large gaps to form in the intergranular gaps in the matrix, and cracks will preferentially expand from there when compressed, resulting in reduced strength.

[0037] The carbon dioxide-based building material obtained by the preparation method provided by the present invention has high strength and porous structure characteristics, and contains 15-70wt% calcium carbonate. Among them, the flexural strength is 5-30Mpa; the average pore size is 6-20nm; the specific surface area is 7-20m 2 ·g -1 ; Total pore volume is 0.02~0.04cc·g -1 .

[0038] Different from traditional geological storage and mineralization maintenance, the present invention proposes for the first time to directly mineralize the CO2 capture liquid into carbonates in a homogeneous phase, avoiding the high energy consumption caused by the desorption of CO2 capture liquid into CO2 gas, directly selecting the capture liquid as the CO2 source, shortening the carbon chain of the overall process, improving utilization efficiency and reducing costs. At the same time, the present invention simulates the cement hardening mechanism, adding part of the waste glass powder to the mineralized product to provide silicon, generating calcium silicate hydrate through hydrothermal curing reaction, and converting the CO2 fixation material into a high-strength building material to achieve its storage, fixation and resource reuse, realizing the cycle concept of CO2 coming from nature and used for nature.

[0039] The technical solution provided by the present invention realizes the stable storage and resource reuse of the huge amount of calcium-containing and silicon-containing minerals on the earth in coordination with the large amount of carbon dioxide emitted. It can not only store a large amount of carbon dioxide, but also reuse it as a building material, which has industrial value. Moreover, since CO2 is evenly distributed inside the material in the form of calcium carbonate, rather than mineralized on the surface, it has a higher CO2 solidification rate (>25%).

[0040] The following examples are further listed to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values ​​​​exemplified below.

[0041] Example 1

[0042] The method for preparing carbon dioxide-based building materials by mineralizing carbon dioxide capture liquid is as follows: (1) Mineralization reaction. The solid waste carbide slag is crushed, ground and dried at 80°C for 24 hours. Then, the corresponding carbon dioxide capture liquid and the ground and dried carbide slag raw material are taken according to the liquid-solid ratio of 4 mL / g, added into a solid-liquid homogeneous reactor, and subjected to room temperature mineralization reaction for 1 hour under stirring conditions of 1000 r / min. After the reaction, liquid-solid separation is performed, and the solid is dried to obtain a calcium carbonate mineralization product; (2) Hydrothermal consolidation. The crushed and ground mineralized product (60%) and waste glass powder (40%) were weighed according to a certain mass percentage, and then 15% of the total mass of the mineralized product and the waste glass powder was weighed in deionized water, and the mixture was fully ground and mixed to form a slurry, which was then pressed into a 40 mm × 15 mm × 5 mm green body at a molding pressure of 30 MPa. After demolding, the green body was placed in a hydrothermal reactor for hydrothermal curing at a hydrothermal temperature of 200 ° C and a hydrothermal time of 9 h. The hydrothermally cured block was dried for 24 h to obtain a carbon dioxide-based building material.

[0043] The carbon dioxide-based building material prepared by Example 1 of the present invention has high strength and porous structure characteristics, with a flexural strength of 22.3 Mpa; an average pore diameter of 8.30 nm, and a specific surface area of ​​19.48 m 2 ·g -1 ; Total pore volume is 0.04cc·g -1 ; The carbon dioxide-based building material contains 50wt% calcium carbonate.

[0044] Example 2

[0045] The preparation method of this Example 2 refers to that of Example 1, with the main difference being that different liquid-to-solid ratios (1 mL / g, 2 mL / g, 6 mL / g, 8 mL / g, 10 mL / g) of carbon dioxide capture liquid and carbide slag were selected to study the effect of liquid-solid contact area on the homogeneous mineralization reaction in step (1).

[0046] Calcium carbonate decomposes and loses weight at 550-900℃, and the weight loss is the amount of CO2. Therefore, by measuring the mass difference between the sample at 550℃ and 900℃, the carbon (CO2) content of the sample can be obtained. The content of calcium carbonate in the mineralized product obtained under different liquid-solid ratio conditions, that is, the carbon (CO2) content, is calculated by thermogravimetric analysis. The calculation method is: ω=(m2-m1) / (m1-m0)×100% Wherein, ω (%) is the carbon content of the mineralized product sample, m0 is the mass of the mineralized product sample at 25°C, m1 is the mass of the mineralized product sample at 550°C, and m2 is the mass of the mineralized product sample at 900°C.

[0047] Figure 1 Schematic diagram of carbon content of homogeneous mineralization products under different liquid-to-solid ratios in Examples 1 and 2. Figure 1It can be seen that the liquid-solid ratio has a great influence on the mineralization CO2 of carbide slag. When the liquid-solid ratio is relatively low (liquid-solid ratio = 1mL / g), the liquid component is relatively small, the liquid-solid contact area is small, and the mineralization process will be incomplete. However, due to the excellent activity of carbide slag itself, the carbon content can reach 27.5% when the liquid-solid ratio is 1mL / g, indicating that the mineralization product already contains 62% of calcium carbonate products. At this time, due to the low liquid-solid contact area and the low degree of material exchange, the calcium in the carbide slag and the carbonate ions in the carbon dioxide capture solution are not easy to pass through the product layer to combine, so the Ca conversion rate is low. As the liquid-solid ratio continues to rise, the carbon content shows a trend of first increasing and then slightly decreasing. When the liquid-solid ratio increases from 1mL / g to 2mL / g, the carbon content has a sudden increase, indicating that the liquid-solid contact area has a sudden change at this time, and the reaction process of the carbide slag particles and the ammonium carbonate solution has increased. After that, as the liquid-solid ratio increases, the carbon content only rises slowly. When the liquid-solid ratio is 6 mL / g, the carbon content reaches a maximum value of 39.9%. At this time, the mineralized product contains 90.7% calcium carbonate, which is 91% of the highest theoretical carbon content (44%). When the liquid-solid ratio is between 4 and 8 mL / g, the carbon content of the products of the homogeneous mineralization reaction is above 35%, and the content of the calcium carbonate product is above 80%. Considering the conversion rate and industrial operation of the ammonium carbonate solution, a relatively preferred liquid-solid ratio of 4 mL / g can be used for subsequent reactions.

[0048] Example 3

[0049] The preparation process of this Example 3 refers to that of Example 1, with the main difference being that different mineralization times (2h, 4h, 8h, 16h) were selected to explore the changes in mineralization products at different reaction times, so as to study the chemical process and main influencing factors of the homogeneous mineralization reaction in step (1), and to explore the specific reaction flow of the mineralization process.

[0050] Figure 2 Schematic diagram of carbon content of homogeneous mineralization products at different mineralization times in Examples 1 and 3. Figure 2It can be seen that under the condition of liquid-solid ratio of 4mL / g, the carbon content in the mineralized product has reached 36% in just 1 hour of reaction, which is 82% of the highest theoretical carbon content. This further shows that the mineralization activity of carbide slag is excellent and it is very suitable for mineralization reaction. After that, with the increase of reaction time, the carbon content of the product only increased slowly. When the reaction time was extended to 16 hours, the carbon content was close to 40%. The extension of reaction time did not bring about a significant increase in carbon content, indicating that the mineralization reaction has basically reached equilibrium after 1 hour. In the early stage of mineralization reaction (<1h), due to the appropriate liquid-solid ratio, calcium ions quickly combined with carbonate ions to form calcium carbonate precipitation and deposited on the surface of particles; in the middle stage of reaction (1-2h), due to the continuous accumulation of calcium carbonate in the product layer, its thickness increased, resulting in an increase in the difficulty of diffusion of calcium ions and carbonate ions, so that the carbon content increased slowly; in the late stage of reaction, the thickness of the dense product layer brought resistance so that ions could not diffuse, carbonate ions could not combine with calcium ions, and the mineralization reaction reached equilibrium. Therefore, according to the above analysis, a 1-hour reaction time is relatively optimal for homogeneous mineralization reaction at room temperature, which can achieve a higher product carbon content while ensuring the mineralization efficiency to meet industrialization requirements.

[0051] Characterization of the microscopic crystal form, morphology and mineral composition of mineralized products. The microscopic crystal form and morphology of mineralized products are extremely important. The mineral composition of the product is determined by the microscopic crystal form and the main components of the mineralized product are confirmed. The mineralized product is mainly calcium carbonate, of which calcite is the most stable phase. Therefore, calcite should be the main component of the mineralized product to ensure that CO2 can be stably sealed.

[0052] The mineralized product prepared in Example 1 was analyzed by SEM. Figure 3 This is a SEM image of the homogeneous mineralization product sample prepared in Example 1. Figure 3 It can be seen that there are two main types of minerals in the mineralization products: blocky minerals and slender rod-shaped minerals. The blocky minerals are calcite-type calcium carbonate, while the slender rod-shaped minerals are aragonite-type calcite. As can be seen from the figure, the mineralization products are mainly calcite, and its crystal form is complete, which shows that CO2 in ammonium carbonate can be directly mineralized into the most stable calcium carbonate in one step without the need for high-energy-consuming processes such as analytical purification, which can shorten the carbon chain structure and optimize the overall process efficiency.

[0053] Example 4

[0054] The preparation method of this Example 4 refers to that of Example 1, with the main difference being that different waste glass powder dosages (30%, 50%, 60%, 70%) were selected to observe the change in the flexural strength of the carbon dioxide-based building materials obtained under the conditions of different waste glass powder dosages in step (2), and to analyze the dissolution of silica inside the materials.

[0055] Figure 4Schematic diagram of the change in flexural strength of carbon dioxide-based building materials under different waste glass powder dosages in Examples 1 and 4. Figure 4 It can be seen that when the ratio of mineralized products to waste glass powder is large (i.e., the amount of waste glass powder added is very small), the solidified body is mainly composed of calcium carbonate products. Therefore, the amount of silicon dissolved and precipitated from the glass powder particles under the hydrothermal environment is very small. Although there is a lot of calcium at this time, it cannot be combined in the gaps between particles to form hydrated calcium silicate or the amount generated is very small. Therefore, the mineralized product particles are difficult to be cross-linked by the hydrated calcium silicate product and cannot form a hard matrix. Therefore, the strength of the sample is extremely low when the amount of waste glass powder added is small. When the content of waste glass powder increases to 30wt%, part of the silicon can be precipitated during the hydrothermal process and hydrated calcium silicate products can be generated, so that the strength rises to 13MPa; then as the content of waste glass powder continues to increase, the amount of hydrated calcium silicate products generated increases sharply, so the strength of the sample rises rapidly. When the amount of waste glass added is 50wt%, the flexural strength of the solidified body reaches a maximum value of 22.7Mpa. It should be noted that when the waste glass content is 40wt%, the flexural strength of the solidified body is slightly lower than that of the content of 50wt%. However, in order to make the final product contain more calcium carbonate and obtain a higher carbon dioxide disposal amount, in actual production, a usage ratio of 60% mineralized product to 40% silicon raw material is generally preferred. Furthermore, when the ratio of mineralized product to waste glass powder is small (the content of waste glass powder exceeds 80wt%), the solidified body is mainly composed of large particles of glass. At this time, the calcium-silicon ratio is relatively low, and the structural strength of the glass body itself is weak, resulting in less calcium silicate hydrate products. Therefore, cracks are likely to appear in the glass body inside the solidified body when under pressure, causing overall cracking, and the strength of the solidified body will be sharply reduced.

[0056] Example 5

[0057] The preparation method of this Example 5 refers to that of Example 1, with the main difference being that different hydrothermal temperatures (100°C, 120°C, 140°C, 160°C, 180°C, 220°C) were selected to observe the change in the flexural strength of the carbon dioxide-based building materials obtained under different hydrothermal temperature conditions in step (2), and to analyze the dissolution of silica inside the materials.

[0058] Figure 5 Schematic diagram of the change in flexural strength of carbon dioxide-based building materials at different hydrothermal temperatures in Examples 1 and 5. Figure 5It can be seen that the flexural strength of the solidified body has a mutation point with the increase of reaction temperature, that is, 180℃. When the reaction temperature is lower than 180℃, the sample has only a very low strength (1-3MPa) after hydrothermal curing. When the reaction temperature exceeds 180℃, the sample strength rises rapidly. When the reaction temperature is 200℃, the highest strength value of 24.3MPa appears, and then it decreases slightly. Combined with the effect of hydrothermal temperature on the dissolution degree of silica, the existence of the mutation point may be due to the fact that the activation energy of silicates in the glass powder needs to be higher than 160℃. When the temperature is lower (<180℃), the surface activation energy of the particles is not enough to stimulate the gradual dissolution of the particles, or only a very small number of particles have a high surface activation energy and partially dissolve, but the amount of silica dissolved is too small, resulting in the inability to generate hydration products. The particles are still in a simple stacking state, not cross-linked, and very easy to crack. When the reaction temperature reaches the level that can stimulate large-scale dissolution of the particle surface (≥180℃), a large amount of silica dissolves into the liquid phase, and hydration products are precipitated, which further cross-link and fill the pores, so that the particles form a whole and the strength rises rapidly. As the temperature rises excessively, a large amount of silica dissolves, the crystals grow excessively, squeezing the pores, causing internal stress and making the sample more prone to cracking.

[0059] Example 6

[0060] The preparation method of this Example 6 refers to that of Example 1, with the main difference being: different hydrothermal reaction times (0h, 3h, 6h, 12h) were selected to observe the change in the flexural strength of the carbon dioxide-based building material obtained under the conditions of different hydrothermal reaction times in step (2), and to analyze the dissolution of silica inside it.

[0061] Figure 6 Schematic diagram of the change in flexural strength of carbon dioxide-based building materials (solidified blocks) at different hydrothermal reaction times in Examples 1 and 6. Figure 6 It can be seen that the hydrothermal reaction time determines the degree of silica dissolution and the amount of new minerals generated. In the hydrothermal system, silica will undergo a large-scale dissolution-precipitation process, causing a sudden increase in the strength of the solidified block. Figure 6 It shows that it takes about 9 hours for the silicon in the solidified body to undergo a large-scale dissolution-precipitation process. The hydrothermal activity of silicon is lower in a system with a longer reaction time. When the reaction time is less than 6 hours, the degree of silicon dissolution is low, only a small amount of hydration products can be produced, and the strength increases slowly. When the reaction time is appropriate (about 9 hours), a large amount of silicon dissolves and precipitates a large amount of hydration products, causing a sharp increase in strength. After that, the reaction time is extended to cause excessive growth of crystals, resulting in a certain degree of reduction in strength.

[0062] The hydrothermal process is a dissolution-precipitation process, in which dissolution is the most important and time-consuming process. Within 0 to 3 hours, the glass powder particles are in a slow dissolution process, and the slow dissolution process results in the ineffective generation of hydration products. Within 3 to 6 hours, the dissolution rate of the glass particles accelerates, but only part of the dissolution occurs, and only CSH gel can be formed in a short time. At the same time, CSH gel can cross-link particles and strengthen the matrix, so the strength is significantly improved. Within 6 to 9 hours, a large number of glass particles are dissolved, and the generated CSH gel begins to transform into minerals with better crystal forms such as tobermorite and sodium zeolite. It relies on the surface of the particles to form needle-shaped and plate-shaped crystals, which firmly fix the particles, so the matrix has a significant increase. Within 9 to 24, the hydration products formed in the early stage continue to grow. As they gradually develop and become complete, the sample strength reaches the maximum value. After that, the hydration products continue to grow, resulting in excessively large grains and poor integrity of the crystal structure, which generates expansion internal stress inside and reduces the strength.

[0063] The XRD patterns of the solidified blocks obtained with different hydrothermal times were studied, and the strength enhancement mechanism and the existence of calcium carbonate crystals inside the solidified bodies were analyzed.

[0064] Figure 7 XRD diagram of solidified block samples obtained under different hydrothermal solidification time conditions in Example 1 and 6. As can be seen from the figure, when the reaction time is less than 9 hours, the main mineral in the sample is calcite, and no other obvious new minerals are found; after the reaction time reaches 9 hours, at 2θ=28~30°, a small diffraction peak appears next to the calcite diffraction peak, which is the diffraction peak of CSH, and as time goes by to 12 hours, the diffraction peak intensity of CSH continues to increase, indicating that the crystal form of CSH is gradually complete and the amount of generation is large at this time, corresponding to which the flexural strength of the sample at this time shows a trend of first increasing and then decreasing. This is mainly because the newly generated CSH can cross-link particles, fill pores, optimize the pore structure, and form a whole inside the solidified body, so the strength is greatly improved. However, with the generation and continuous development of a large number of CSH, coarser mineral particles are filled in the pores, forming internal stress, resulting in a decrease in the strength of the solidified body. Therefore, the strength enhancement of the solidified body is provided by the generated hydrated calcium silicate CSH. At the same time, the strongest diffraction peak in the XRD spectrum of the solidified bodies obtained at different hydrothermal times is always the diffraction peak of calcite-type calcium carbonate, and its half-peak width is narrow, which indicates that the calcium carbonate crystals in the CO2 fixed material can stably exist in the solidified body after hydrothermal treatment, and its crystal form is complete, and no crystal destruction or crystal form transformation will occur due to the hydrothermal process.

[0065] The actual amount of solidified CO2 in the hydrothermally solidified block indicates how much negative carbon effect each sample can have. Thermogravimetric analysis can effectively explore whether the main component of the mineralized product, calcium carbonate, undergoes a large-scale decomposition process during the hydrothermal process, and the actual amount of CO2 solidified in the hydrothermally solidified block. The following thermogravimetric analysis is used to further illustrate the CO2 solidification amount of the hydrothermally solidified block.

[0066] The carbon dioxide-based building material samples in Examples 1 and 6 were crushed and ground, and the powder under the 200-mesh sieve was dried at 80°C for 24 hours. Then, a thermogravimetric analysis was performed using a STA449C synchronous thermal analyzer from NETZSCH, Germany, with a temperature range of 25 to 1000°C, a heating rate of 10°C / min, and a nitrogen atmosphere protection with a nitrogen flow rate of 50 mL / min.

[0067] Figure 8 This is the thermogravimetric analysis diagram of the solidified block sample prepared under the condition of 9h hydrothermal solidification time in Example 1. It can be seen from the figure that the sample has three stages of weight loss process, which are 80-150℃, 200-300℃ and 550-850℃ respectively. The first stage is the loss of free water and mineral interlayer water. The hydrothermal precipitation product is mainly hydrated silicate, whose layered or island structure adsorbs interlayer water, mainly relying on van der Waals force to maintain stability, and the bond strength is weak, which is easily destroyed at 100-150℃. The second stage is the structural water of the mineral structure, also known as the dehydroxylation of chemical water. It is bonded to the atoms in the mineral structure with a fixed coordination ratio and content ratio, and the bond energy is much higher than the interlayer water bond energy, so a higher temperature is required for dehydroxylation to occur. The third stage is the decomposition process of calcium carbonate, which will gradually decompose between 550-800℃, release CO2, and transform into CaO components, and its mass loss is the amount of CO2. According to the weight loss of the sample between 550 and 900°C, the CO2 content of the sample with a 40% glass powder addition ratio is calculated to be 21.53%. If the theoretical CO2 content is calculated based on pure calcium carbonate, it is 24.26%, and the difference between the two is only 2.73%. The difference between the two comes from the presence of some impurities in the calcium carbonate reagent and free water and bound water. This verifies that the main component of the mineralization product - calcium carbonate can exist stably in a relatively low-temperature hydrothermal environment without large-scale decomposition. Only a very small part is destroyed due to providing calcium to form calcium silicate hydrate. Therefore, the idea of ​​converting CO2 into calcium carbonate products and then hydrothermally solidifying them into building materials is feasible. CO2 can be stably sealed in the solidified body and can be used in large quantities as a building material.

[0068] The existence form of CO2 in the hydrothermal solidification block is worth studying, among which CO3 2- This form is the most stable state of CO2 in nature and is also the most desirable form for mineralization storage.

[0069] By performing X-ray photoelectron spectroscopy analysis on the samples before and after hydrothermal treatment, the chemical state of the C element in the products before and after hydrothermal treatment was studied, and the existence form of CO2 in the solidified block after hydrothermal treatment was analyzed. The specific analysis plan is as follows: The untreated embryo and the hydrothermally cured body after 9 h of hydrothermal reaction in Example 1 were crushed and ground, and the powder under the 200-mesh sieve was dried for 24 h. The XPS spectrum of the sample was obtained using an Escalab 250Xi X-ray photoelectron spectrometer from Thermo Fisher Scientific, USA, and the CO3 content inside the sample before and after the hydrothermal reaction was calculated. 2- The content.

[0070] Combined with Table 1 below, it can be seen that the C element in the sample has three chemical states before and after the hydrothermal reaction, namely CC, CO and CO3 2- From the atomic percentage, it is found that CO3 2- The peak ratio remained basically unchanged, while the CC peak content decreased and the CO peak content increased, indicating that CO3 2- The structure is stable, but the CC bond is partially broken under the hydrothermal environment, generating C-OH bonds, which leads to an increase in the CO peak content. This shows that the carbonate structure of the mineralized product obtained by the homogeneous mineralization reaction of ammonium carbonate solution is not destroyed after hydrothermal solidification into building materials, that is, CO2 can be converted into the most stable carbonate in one step through the homogeneous mineralization process, and can be stored and reused as a resource in the form of carbonate. Table 1 Binding energy (eV) and atomic percentage (%) of C element in the green embryo without hydrothermal treatment and the sample after hydrothermal treatment for 9 h

[0071] The technical principle of the present invention is described above in conjunction with specific embodiments. These descriptions are only for explaining the principle of the present invention and cannot be interpreted as limiting the scope of protection of the present invention in any way. Based on the explanations herein, those skilled in the art can associate other specific implementations of the present invention without paying creative labor, and these methods will fall within the scope of protection of the present invention.

Claims

1. A method for preparing carbon dioxide-based building materials by mineralizing carbon dioxide capture liquid, characterized in that: The method comprises the following steps: The carbon dioxide capture liquid and the calcium-containing raw material are subjected to a solid-liquid homogeneous mineralization reaction to obtain a calcium carbonate mineralization product; The calcium carbonate mineralization product, silicon-containing raw materials and solvent are mixed to form a slurry, which is then formed and demolded to obtain a demolding body, and then the demolding body is subjected to a hydrothermal reaction to obtain the carbon dioxide-based building material.

2. The method according to claim 1, characterized in that The carbon dioxide capture liquid is an ammonium carbonate solution, and the mass fraction of the ammonium carbonate solution is 10-40wt%, preferably 33wt%.

3. The method according to claim 1 or 2, characterized in that: The calcium content of the calcium-containing raw material is 10-54wt%; preferably, the calcium-containing raw material is solid waste carbide slag, fly ash, steel slag; more preferably, the particle size of the calcium-containing raw material is 3-100μm, and the average particle size d 50 It is 17.57μm.

4. The method according to any one of claims 1 to 3, characterized in that The usage ratio of the carbon dioxide capture liquid to the calcium-containing raw material is 1-10 mL / g, preferably 4 mL / g.

5. The method according to any one of claims 1 to 4, characterized in that The temperature of the solid-liquid homogeneous mineralization reaction is 25-80°C, and the time is 1-16 hours, preferably 1-12 hours, and more preferably 1 hour.

6. The method according to any one of claims 1 to 5, characterized in that The silicon content in the silicon-containing raw material is 10-46.7wt%; preferably, the silicon-containing raw material is waste glass powder obtained by crushing and grinding daily glass slag, and the chemical composition of the waste glass powder preferably includes: SiO268.09%, Na2O 17.37% by mass percentage; the particle size of the silicon-containing raw material is distributed in the range of 60-120μm, and the preferred average particle size is 88.9μm.

7. The method according to any one of claims 1 to 6, characterized in that Taking the total mass of the mineralized product and the silicon-containing raw material as 100%, the mass of the mineralized product accounts for 30-70%, preferably 60%, and the mass of the silicon-containing raw material accounts for 70-30%, preferably 40%; the solvent accounts for 5-15% of the total mass of the mineralized product and the silicon-containing raw material.

8. The method according to any one of claims 1 to 7, characterized in that The temperature of the hydrothermal reaction is 100 to 220° C., preferably 120 to 220° C.; the time of the hydrothermal reaction is 3 to 12 hours, preferably 6 to 12 hours, and more preferably 9 hours.

9. A carbon dioxide-based building material prepared according to the method of any one of claims 1 to 8.

Citation Information

Patent Citations

  • A method for curing concrete blocks using carbon dioxide step mineralization

    CN108340480B

  • Method for mineralization storage of CO2 through magnesium resources in serpentine

    CN109399675A